Pengaruh Intellectual Capital, Efisiensi Operasional, Profitabilitas dan Good Corporate Governance Terhadap Nilai Perusahaan - Intan Kusuma Widyandari; Fatchan Achyani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of Intellectual Capital, Operational Efficiency, Profitability, and Good Corporate Governance on company value in the consumer goods industry sector listed on the Indonesia Stock Exchange for the period 2021-2023. A quantitative approach with a comparative causal design is used, with secondary data in the form of financial reports obtained through purposive sampling so that the sample obtained is 93 companies. Data analysis includes classical assumption tests and multiple linear regression to test the effect of independent variables on company value. The results of the study indicate that only Profitability has a significant effect on company value, while Intellectual Capital, Operational Efficiency, and Good Corporate Governance do not have a significant effect. This study contributes to understanding the factors that influence company value in the consumer goods industry sector and becomes the basis for further research to include additional variables and expand the observation period..